SOCIALIZATION OF DIGITAL ENTREPRENEURS FOR GENERATION Z AT SULTAN AGUNG PEMATANGSIANTAR PRIVATE HIGH SCHOOL - Sherly, Sherly; Halim, Fitria; Augustinah, Fedianty; Dharma, Edy; Sudirman, Acai (LPPM Univ. Ibn Khaldun Bogor, 2023)
The urgency of this community service activity with the theme of Socializing Digital Entrepreneurs for Generation Z at Sultan Agung Pematangsiantar Private High School is to provide knowledge about digital entrepreneurs and training on applying digital marketing using the E-Commerce platform. The method used to implement this activity is through lectures and direct practice of implementing digital entrepreneurs. The stages of implementing this event include the opening and introduction of digital entrepreneurs, presentations on digital entrepreneurs, presentations on several problems often faced by digital entrepreneurs, then continued with practices related to digital marketing. After the service activities were completed, a follow-up interview was conducted regarding the impact of implementing the service activities